Constitution and Preservation: Experiences of the Grand Duchy of Lithuania - Kuolys, Darius (Problemos, 2020)
By refering to the examples of different cultural traditions, Arūnas Sverdiolas in his study Constitution and Preservation described the mechanisms that are involved in the creation of culture – constitution and preservation. The goal of this article is to show how these mechanisms operated in the reality of the Grand Duchy of Lithuania. The article analyzes the roles that the Lithuanian political society gave to legislation, upbringing, historical narratives, heroic and occasional poetry while constituting and preserving itself.